Efectos de la actividad física en las relaciones interpersonales en niños con Síndrome de Down. - Lara Simba, Andrea Carolina (2023)
The purpose of the current study is to examine how physical activity affects social interactions in Down syndrome kids at the "Despertar de Los Angeles" comprehensive care facility. We used a sample of 19 kids divided into two groups for our qualitative, experimental study. We implemented a physical activity program that included a twelve-week planning intervention that was assessed with the tool (Interpersonal Relationship Questionnaire - CERI); pre and post interventions that focused on enhancing interpersonal relationships through cooperative games. Giving as a result of the data obtained from the 5 blocks of the questionnaire (CERI) and through the application of a normality test, after observing the data of our sample < 30; it is determined that the data does not have a normal distribution Pval. < 0.05, applying a non-parametric statistic to mark a before and after using the Wilcoxon test; therefore, in the experimental group a result of Pval. < 0.00 this means that it has a very significant valuation; meanwhile, in the control group, a result > 0.05 is obtained, where it is shown that there has been no significant change. It was concluded that a Pval 0.01 was achieved and demonstrating a real value P = 0.00 was demonstrated when evaluating children with Down syndrome through the study conducted, of a physical activity program that is focused on cooperative games and with the application of the questionnaire (CERI), which shows that there was a very significant improvement in the development of interpersonal relationships.